The management of other aspects of chronic liver disease, including transplantation - McCashland, Timothy M. (Henry Stewart Talks, 2011)
Common complications of end stage cirrhosis including life threatening disorders of variceal bleeding, ascites, hepatorenal syndrome, encephalopathy and hepatopulmonary syndrome, Preparation for listing for liver transplantation in patients with end stage liver disease includes documentation and absence of alcohol consumption (in alcoholics), reduction of hepatitis B DNA levels (in HBV patients) and aggressive treatment of hepatocellular carcinoma to reduce the risk of recurrent disease, The most common allocation system for liver transplantation is the model for end stage liver disease, Post transplantation care of the patient requires diligent annual followup with concentration on common diseases which include: metabolic syndrome (diabetes mellitus, obesity, hypertension, hyperlipidemia), Preventive medicine (vaccination, dental disease), Inflammatory bowel disease, bone disease, and renal dysfunction
Archived at 2021/09/30